PENDEKATAN PEMERINTAH MENDORONG KESADARANWAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN(PBB - Rohman, Abd.; Adiwidjaja, Ignatius (Publicio: Jurnal Ilmiah Politik, Kebijakan dan Sosial, 2022)
The research problems are low public awareness to pay PBB, clear evidence of the benefits of development from PBB, and the lack of enthusiasm by officials to collect PBB. This study aims to determine the village government's efforts to increase public awareness to pay PBB. The research method used was qualitative with data collection techniques using interviews, observation, documentation, and literature related to the research focus. Data were analyzed using the interactive Miles, Huberman, and Saldana models. The results of the study show that increasing public awareness in paying PBB is carried out by holding intense outreach on various occasions. Collaborating with community leaders to provide an understanding of the importance and benefits of PBB, making it easy for people to pay PBB by opening payment counters at the Village Office, and making efforts to improve community data that does not match real conditions on the ground. Factors that influence people's apathy and reluctance to pay taxes are tax data discrepancies with conditions in the field, as well as inadequate facilities. As a recommendation for improvement, there needs to be intense assistance from village officials to provide awareness for the community.